Contribuição da implementação de sistema de gestão da qualidade fundamentado na NBR ISO 9001:2000 sobre a gestão de suprimentos em canteiros de obra na construção civil cearense - Linard, Roberto Sérgio Sobreira (2008)
This research has for objective to identify contributions to the supply management in the construction sites caused by the adoption of Quality System based on NBR ISO 9001:2000. The construction companies search to improve their methods intended to reduce costs. The Quality Systems implementation in civil construction companies has itself shown practicable. The possibility to guarantee adequate material resources, at the opportune moment and in the necessary place constitutes important way to the search for companies’ competitiveness. There are requisites in NBR ISO 9001:2000 that demands on the company actions implemented for routines utilization as: correct material specification, control in the act of receiving of these in the construction sites and management about the adequate storage and handling. These are elements that can gain profits to the supply management in the construction sites. This research was divided in stages. It firstly was accomplished bibliographical research, soon after was developed the research instrument, which was applied to the companies. The data were collected and analyzed, subsidizing thus the conclusions. The research demonstrated that the Quality System implementation based on NBR ISO 9001:2000 contributes to the work sites supply management in the civil construction. Thus, the implementation of the related Quality Systems causes positive contributions to the civil construction industry, assisting it in the search to eliminate waste and losses, becoming it more competitive